TEACHERS' ATTITUDES TOWARDS THE IMPLEMENTATION OF EXTRAMURAL ENGLISH (EE) IN ENGLISH AS FOREIGN LANGUAGE (ELT) - Yulitriana, Yulitriana; Emeral, Emeral; Karani, Elanneri; Susanty, Susanty; Syeba, Sulamit; Aderia, Rikha; Wulansari, Angely Eunike (Universitas Muhammadiyah Metro, 2025)
Teachers have essential roles in facilitating ELT, and their attitudes towards the approaches applied will contribute to the success of language learning. The objective of this research was to examine teachers' attitudes towards the implementation of Extramural English (EE) in ELT. One-shot survey research was conducted in rural areas of a regency in Central Kalimantan, Indonesia, with 60 high school English teachers participating as the sample. A survey incorporating both closed- and open-ended questions was administered to gather data. The data analysis involved calculating the percentages from the closed-ended responses, followed by a detailed explanation of the teachers' answers to the open-ended questions. The findings indicate that most teachers have integrated Environmental Education (EE) activities throughout all phases of English Language Teaching (ELT). They employ EE, particularly in conjunction with Technology, due to its ability to broaden their knowledge, improve their skills, effectively engage students' interests, and facilitate English learning. Furthermore, the advantages of utilizing EE significantly surpass the associated challenges. Therefore, developing English Language Teaching (ELT) to meet students' English as an additional language (EAL) needs is crucial, as EAL plays a significant role in students' language development. In conclusion, teachers have a positive attitude towards implementing English Education (EE) in English Language Teaching (ELT) since it positively contributes to ELT.